Automorfismos de límites de Fraissé con clases de conjugación densas (2017)
"The objective of this dissertation is to study several FraÅssú clases, construct they're limits and verify the existence of generic automorphisms. More specifically the existence of generic automorphisms will be prooven for the following families: vector spaces over Fp, finite lineal orders, finite sets, finite graphs and finite metric spaces. Lastly the existence of ample generic automorphisms will be verified for the following families: vector spaces over Fp, finite sets, finite graphs and finite metric spaces. For the finite order family the non existence of such an automorphism will be proven." -- Tomado del Formato de Documento de Grado.